El webdoc como herramienta en la lucha por la igualdad: En la brecha (2018) del Lab RTVE - Dra. María Purificación SUBIRES MANCERA (Fonseca, Journal of Communication, 2023)
The webdoc, as an interactive and multimedia evolution of the cinematographic and television documentary, born with the development of the Internet, keeps the same essence of its precedents: its informative and denouncing character and its critical vision of reality.This paper analyses, using the case study methodology, the webdoc En la brecha, by RTVE Lab, which was created to celebrate the International Equal Pay Day, in 2018, and through which it was intended to denounce the existing salary gap –hence the title of the webdoc– between women and men in their average annual salary